VERTICAL PARTITIONING RELATIONS METHOD IN RELATIONAL DATABASE - NGO THANH HUNG (Advanced Engineering Research, 2008)
In this paper we introduce a new objective function for vertical partitioning relations in relational databases. It has been built with the new evaluative criterion: cache hit probability. Also present heuristic algorithm for finding the optimal partitioning schema.